THE INFLUENCE OF LEADERSHIP STYLE, COMMUNICATION, MOTIVATION, AND WORKLOAD ON JOB SATISFACTION - Nurhanifah, Salma; Widhiandono, Hengky; Darmawan, Akhmad; Haryanto, Totok (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACT The purpose of this study was to examine and analyze the effect of leadership style, communication, work motivation, and workload on employee job satisfaction at the Office of the Ministry of Agrarian Affairs and Spatial Planning of the Land Agency (ATR/BPN) of Cilacap Regency. This type of research is a quantitative-survey research. The population in this study were all ATR/BPN employees in Cilacap Regency. Samples were taken using the slovin formula, totaling 108 employees at ATR/BPN Cilacap Regency. The sampling technique in this study used the Simple Random Sampling (SRS) technique. The research instrument used a questionnaire. The analysis technique in this study uses statistical analysis Smart Partial Least Square (Smart-PLS) 3.2.9 is used to test validity, reliability test, R-Square test, Net Fit Index (NFI) test, and hypothesis testing. The results of this study prove that partially leadership style, communication, work motivation affect job satisfaction of ATR/BPN employees in Cilacap Regency, while workload partially does not affect job satisfaction of ATR/BPN employees in Cilacap Regency.Keywords: Leadership Style, Communication, Motivation, Workload, Job Satisfaction